African and Asian Medicinal Plants as a Repository for Prospective Antiviral Metabolites Against HIV-1 and SARS CoV-2: A Mini Review - Anywar, Godwin; Akram, Muhammad; Chishti, Muhammad Amjad (Frontiers in Pharmacology, 2021)
Introduction: The worldwide burden of viral infection has triggered a resurgence into the search for new and more efficient antiviral medicines. Scientists are also repurposing existing natural compounds as potential drug candidates for of the emerging and re-emerging viral infections especially Aim: The aim of this mini review was to analyse the existing literature to explore actual or potential natural antiviral compounds from plants as lead compounds in the drug discovery process. Methods: We searched the literature on African and Asian medicinal plant species as antiviral agents especially for HIV-AIDS and SARS-CoV-2 in various databases and search engines such as Web of Science, Google Scholar and PubMed. Results: We present a list of 13 plant species with potential or promising antiviral activity especially against HIV-1 and the novel coronavirus strain (SARS-CoV-2). These plant species span the continents of Africa and Asia where they are widely used for treating several other ailments. Conclusion: Natural compounds from plants can potentially be beneficially clinically in treating or managing various viral infections plaguing humanity. More research needs to be conducted to investigate the potential toxicities of the various compounds and their efficacy in clinical settings